The factors that influencing customer behavior on servicescape offered by Mutiara Johor Bahru / Mohd Harith Ramli - Ramli, Mohd Harith (Faculty of Business and Management, 2007)
This research was conducted for the purposed of "The Factor That Influencing Customer Behavior on Servicescape Offered by Mutiara Johar Bahru". The main objective of this research was to identify the factors that influence customer behavior on servicescape offered by Mutiara Johor Bahru